(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: The proposed study aims to look at the outcomes of angioembolization in terms of survival, blood transfusions, length of ICU stay, and overall stay, need for surgical exploration. Methods: After the ethical approval from institutional review, this prospective observational study was conducted in the emergency Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT) from ————– to —————-. Through non-probability consecutive sampling, 72 patients aged 18 or above, both genders, with abdominopelvic injury and undergoing angioembolization were included in the study. Clinical outcomes following angioembolization were meticulously recorded, encompassing measures such as mortality rates, rates of successful hemostasis, length of hospital stay, need for surgical intervention, and incidence of complications such as rebleeding or ischemic complications. Results: The average injury severity score of the participants was 29.32±10.16. Technical success and clinical success rates in the present study were 82% and 85% respectively. Rebleed was observed in 4% of the individuals. The average hospital length stay was 43.32±23.2 days. A 15% mortality rate was observed in the present study. Conclusion: Angioembolization is a highly effective procedure that can be used to halt bleeding and provide support for non-surgical treatment of both solid organ damage and pelvic fractures. With meticulous selection and effective implementation, it boasts a remarkable success record.